Influence of Parent and Student Psycho – Social Factors on Learning Outcomes in Economics Among Senior Secondary School Students in Enugu State, Nigeria (2015)
The level of performance of students in economics has become a source of major concern in Nigeria particularly the fluctuating results of Enugu State as released by examining bodies over the years. This had been attributed partly to parent and student psycho-social factors. Experts have evolved several measures to improve students’ performances which have not yielded appreciable outcome. However, these several measures did not include considerations for parent and student psycho-social factors. This study therefore, examined the influence of parent support, socio-economic status and expectation and student psycho-social factors (students’ perception of their parents’ support, self-efficacy and self-regulation) on student attitude and achievement in economics. The study adopted the survey research design. The multi-stage sampling technique was used to select 1,350 students and their parents from 45 proportionately selected secondary schools in the seventeen Local Government Areas of Enugu State. Six validated instruments were used: Parents’ Questionnaire (r = 0.71), Students’ Perception of their Parents’ Support Scale (r = 0.65); Economics Achievement Test (r = 0.69); Students’ Self-Regulation Scale (r = 0.74); Students’ Self-Efficacy Scale (r = 0.74) and Students’ Attitude towards Economics (r = 0.82). Data were analysed using multiple regression and t-test at 0.05 level of significance. There was a significant relationship between students’ perception of their parents’ support and academic achievement (r = .068), and self-efficacy and academic achievement (r = .059). However, the relationship between students’ self-regulation and academic achievement was not significant. The parent and student psycho-social factors accounted for 2.9% of the variance observed in the students’ achievement in economics, while parent factors, when taken together, accounted for approximately 2% of the variance. Specifically, parents’ socioeconomic status (β = .145, t = 5.340) and students’ perception of their parents’ support (β = -.103, t = -3.414) were better than self-efficacy, self-regulation and parent expectation in predicting students’ achievement. Parent’s socio-economic status emerged as the best predictor of academic performance. The students’ variables accounted for 8.6% of the variance observed in the students’ attitude. Self-efficacy (β = .205, t = 3.787), self-regulation (β = .100, t = 3.025) and parent socio-economic status (β = .100, t = 3.787) had significant prediction on students’ attitude. Parent support and socio-economic status contributed positively to student achievement in, and attitude towards economics. Therefore, parents should participate actively in monitoring the school activities of their children while students should be encouraged to be self-regulated as well as be able to monitor their progress. Besides, they should also be encouraged to believe in their capabilities to organise and execute their courses of action.